Floods on the Santa Clara River and Sespe Creek Vicinity of Fillmore, California - US Army Corps of Engineers:::::: (1972)
Supplemental information for Flood Plain Information for the Vicinity of Filmore report. This supplemental information describes the facts of flood potential and flood hazards in the area with pictures illustrating said hazards.